2022
DOI: 10.7759/cureus.31309
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between the Postoperative Complications of Laparoscopic Sleeve Gastrectomy (LSG) and Laparoscopic Roux-en-Y Gastric Bypass (RNYGB) in Patients With Morbid Obesity: A Meta-Analysis

Abstract: The most successful method for treating obesity is bariatric surgery. The two most common surgeries for treating morbid obesity are the laparoscopic Roux-en-Y gastric bypass (RNYGB) and the laparoscopic sleeve gastrectomy (LSG). However, there has not been a thorough analysis of the differences in their adverse effects. The aim of this study was to analyze if RNYGB and LSG had comparable postoperative complications and mortality. To that end, results from trials comparing those who underwent RNYGB and those wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This pattern was maintained until the 12th month (5.8% vs 14.7%, respectively; P = .031). [31] In addition, this study showed that at the 12-month postoperative follow-up, there was a significantly decreasing rate of gallstone formation in the UDCA group compared with control group 4 (4.2%) and 24 patients (25.2%), respectively. And that proved the regular intake of UDCA 6 months after surgery reduced incidence of cholelithiasis after OAGB.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…This pattern was maintained until the 12th month (5.8% vs 14.7%, respectively; P = .031). [31] In addition, this study showed that at the 12-month postoperative follow-up, there was a significantly decreasing rate of gallstone formation in the UDCA group compared with control group 4 (4.2%) and 24 patients (25.2%), respectively. And that proved the regular intake of UDCA 6 months after surgery reduced incidence of cholelithiasis after OAGB.…”
Section: Discussionmentioning
confidence: 76%
“…On the other hand, the incidence of gastroesophageal reflux disease after LSG was greater than that in RYGB. [31] Also, a study confirmed that increase risk of gastroesophageal reflux disease and Barrett esophagus post LSG. [32] The rate of reoperation was higher in the patient who underwent RYGB as compared to those who had LSG.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Enhanced recovery after surgery (ERAS) protocols have revolutionized perioperative care by employing evidence-based practices to enhance patient recovery following surgical procedures [ 1 ]. These protocols encompass a multidisciplinary approach focusing on preoperative, intraoperative, and postoperative interventions to accelerate patient recovery, reduce complications, and shorten hospital stays.…”
Section: Editorialmentioning
confidence: 99%